Rozeff on free banking: a critique. Issue 2 (19th February 2018) - Davidson, Laura; Block, Walter E.
Abstract : Purpose: The purpose of this paper is to correct Rozeff (2010). He contends that fractional-reserve banking is legitimate and efficacious. The authors demonstrate that it is not. Design/methodology/approach: The design of this paper is to quote widely from Rozeff (2010) and then to expose his errors of analysis. Findings: The authors demonstrate that fractional-reserve banking is neither legitimate nor efficacious. Originality/value: Money is the lifeblood of the economy. If so, then banking is the marrow of the economy, since it is from that sector that money arises in the first place. It is crucially important, then, that the monetary system be based on sound principles. Fractional-reserve banking is a violation of these sound principles. Therefore, it is valuable to demonstrate that this is indeed the case.